Comparative Analysis of the Use of Net Base Methods and Gross Up Methods in Article 21 Income Tax Bonds (Article 21 Income Tax) in the form of Employee Salaries - Dewi Anggraini (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study was conducted at PT Surya Agro Persada (SAP) Lubuklinggau City with the focus of research on Income Tax Article 21 and the research sub-focus was the Net Base method and the Gross Up Method. The formulation of the problem in this study is how the comparison of the use of the Net Base method and the Gross Up Method in calculating Article 21 Income Tax is in the form of employee salaries. The purpose is to analyze the comparison of the use of the Net Base method and the Gross Up Method in the context of Article 21 Income Tax in the form of salaries of employees at PT Surya Agro Persada (SAP) in Lubuklinggau City. This research uses qualitative methods, data collection techniques used are observation, interviews and documentation. Based on the results of the analysis carried out that applying the Gross Up method will provide benefits to the company, in addition to providing benefits to employees it can also reduce corporate taxable income because the burden arising from tax benefits can be deductible expenses so that the agency's PPh burden becomes smaller . The conclusion of this study is that the Gross Up method is better than the Net base method, because the calculation using the Gross Up method will benefit both parties, both employees and companies. So it is better for PT Surya Agro Persada to use the Gross Up Method in calculating Article 21 PPh employees. Keywords: Article 21 Income Tax, Net Base, Gross Up